2010
DOI: 10.1037/a0018188
|View full text |Cite
|
Sign up to set email alerts
|

The mating sociometer: A regulatory mechanism for mating aspirations.

Abstract: Two studies (Ns = 80 and 108) tested hypotheses derived from Kirkpatrick and Ellis's (2001) extension and application of sociometer theory to mating aspirations. Experiences of social rejection-acceptance by attractive opposite-sex confederates were experimentally manipulated, and the impact of these manipulations on self-esteem, mating aspirations, and friendship aspirations was assessed. Results indicated that social rejection-acceptance by members of the opposite sex altered mating aspirations; that the cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 58 publications
6
71
1
1
Order By: Relevance
“…Single people are often stereotyped as "sadder" and having a "less exciting" life (Greitemeyer, 2009;Morris et al, 2007) as well as developing factors that destabilize their well-being and quality of life, such as low self-esteem, depression, and sensitivity to rejection (Hirschberger et al, 2002;Kavanagh et al, 2010;Spielmann et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single people are often stereotyped as "sadder" and having a "less exciting" life (Greitemeyer, 2009;Morris et al, 2007) as well as developing factors that destabilize their well-being and quality of life, such as low self-esteem, depression, and sensitivity to rejection (Hirschberger et al, 2002;Kavanagh et al, 2010;Spielmann et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Kavanagh, Robins, and Ellis (2010) observed that self-esteem is infl uenced by romantic rejections, thus resulting in low levels of aspirations for a prospective partner. Hirschberger, Florian, and Mikulincer (2002) found that the level of self-esteem of students was directly proportional to their desired standards in a partner.…”
Section: Miedo a Estar Sola: Evidencias Psicométricas Y De Validez Dementioning
confidence: 99%
“…Frequentemente são atribuídos aos solteiros estereótipos de que estes são "mais tristes" e apresentam uma vida "menos excitante" (Greitemeyer, 2009;Morris et al, 2007), além da possibilidade destes desenvolverem fatores que desestabilizem o seu bem-estar e a qualidade de vida, como baixa autoestima, depressão e sensibilidade a rejeição (Hirschberger et al, 2002;Kavanagh et al, 2010;Spielmann et al, 2013).…”
Section: Discussionunclassified
“…Following this model, during an initial "adolescent" dating and learning phase every time an expression of romantic interest is received from a member of the opposite sex one could raise one's self-appraisal and consequently one's aspiration level for mate search, and lower both after every rejection. This also fits with intuitions about how romantic successes and failures can induce self-esteem to go up and down, which in turn can affect how high or low people aim in their next romantic endeavors (Kavanagh, Robins, and Ellis 2010). In more detail, this aspiration-adjustment heuristic could start all individuals with an initial aspiration level of 50, which corresponds to assuming oneself to be just average.…”
Section: Heuristics For Mate Choice and Searchmentioning
confidence: 96%
“…In other simulations, modifications of this type of aspiration-adjusting mutual search rule have come even closer to matching populationlevel trends in human mating behavior, including correlations between partner characteristics and sex-ratio effects (Simão and Todd 2003). The fact that self-reported individual self-esteem goes up and down with dating success or failure (Kenrick, Groth, Trost, and Sadalla 1993;Kirkpatrick and Ellis 2001;Kavanagh, Robins, and Ellis 2010) points to the psychological plausibility of this aspiration-adjustment heuristic.…”
Section: Heuristics For Mate Choice and Searchmentioning
confidence: 99%